If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 40 + -5x = 4x + 24 Reorder the terms: 40 + -5x = 24 + 4x Solving 40 + -5x = 24 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 40 + -5x + -4x = 24 + 4x + -4x Combine like terms: -5x + -4x = -9x 40 + -9x = 24 + 4x + -4x Combine like terms: 4x + -4x = 0 40 + -9x = 24 + 0 40 + -9x = 24 Add '-40' to each side of the equation. 40 + -40 + -9x = 24 + -40 Combine like terms: 40 + -40 = 0 0 + -9x = 24 + -40 -9x = 24 + -40 Combine like terms: 24 + -40 = -16 -9x = -16 Divide each side by '-9'. x = 1.777777778 Simplifying x = 1.777777778
| n-3=11 | | 3n^3=12n^2 | | n+25=37 | | 60+2x=7x | | -29=9u | | (8+x)/2=10 | | 4t=-76 | | 25x^2-45x+10=0 | | -7x-6=43 | | x^4=13 | | 9p=-27 | | x^2+y^2+8-10y+25=0 | | 2x-9=-9 | | x^42=13 | | -2(3b+3)+(7b-8)=0 | | -5k^2+11k+52=4k | | 6=-6y+3(y+8) | | x-3=10x+30 | | 12x+16=12x-84 | | -7(-15)= | | -12x^2+x=3-4x^2+9x | | (3,-10)= | | 6x-3(x-1)=2x | | -10+4x=-10 | | 2x*3x=2 | | 9+x=5 | | 4(4-n)=6n-4 | | -6=x+3 | | Y-8=-16 | | 2.7q-2.6-1.8q=0.1q-4.3 | | 3r-8=32 | | 2m^2-9m-18=0 |